Uji Kualitas Uji Dokumentasi Terapi Menggunakan Teori Tes Klasik dan Model Rasch - Asyi, Reza Nur (Jurnal Vokasi Indonesia, 2018)
The third-semester occupational therapy students of the University of Indonesia Medical Vocational Program must have occupational documentation competence to explore the information that is available to the patient and determine the purpose of the therapy to be given to become an occupational therapist. The courses taught cannot yet evaluate and analyze student competencies related to occupational therapy documentation. This problem was analyzed using psychology (psychometrics) in the form of Classical Test Theory (CTT) and Rasch Mode. Research respondents were 200 people with a measurement tool for response patterns along with key answers from the Occupation Documentation Final Test, Universitas Indonesia in 2015, 2016 and 2017 consisting of 40 items (35 multiple choice items and five essay items). The method used is non-probability sampling with purposive sampling technique. This study shows that the level of difficulty of the occupational therapy documentation items that are not comparable between Classical Test Theory (CTT) and Rasch Model and Rasch Model is related to the hierarchy of learning subjects occupational therapy documentation.